STARGATE the next evolutionary step toward unleashing the potential of WDM EPONs. - Maier, Martin; Herzog, Martin
WDM EPONs are rapidly becoming mature. In this article we briefly review the state of the art of cost reduction, colorless ONUs, and WDM PONs. We then lift the veil of future WDM EPONs, and elaborate on evolutionary cost-effective upgrades of WDM EPONs and their all-optical WDM integration with Ethernet-based metropolitan area networks to provide transparent connections at the wavelength and sub-wavelength granularity on demand between ONUs residing in different WDM EPONs.
Keywords: Ethernet-based metropolitan area networks; STARGATE; WDM EPON; Colorless ONU; Cost reduction